First, rewrite the expression to make it easier to manipulate:
#2/3(x^4/x^2)(y^-4/y^-y)(z^-3/z^4)#
Next, use this rule of exponents to divide the #x# and #y# terms:
#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#
#2/3(x^color(red)(4)/x^color(blue)(2))(y^color(red)(-4)/y^color(blue)(-y))(z^-3/z^4) =>#
#2/3x^(color(red)(4)-color(blue)(2))y^(color(red)(-4)-color(blue)(-y))(z^-3/z^4) =>#
#2/3x^(color(red)(4)-color(blue)(2))y^(color(red)(-4)+color(blue)(y))(z^-3/z^4) =>#
#2/3x^2y^(-4+y)(z^-3/z^4) =>#
#2/3x^2y^(y-4)(z^-3/z^4)#
Now, use this rule of exponents to divide the #z# term:
#x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))#
#2/3x^2y^(y-4)(z^color(red)(-3)/z^color(blue)(4)) =>#
#2/3x^2y^(y-4)1/z^(color(blue)(4)-color(red)(-3)) =>#
#2/3x^2y^(y-4)1/z^(color(blue)(4)+color(red)(3)) =>#
#2/3x^2y^(y-4)1/z^7 =>#
#(2x^2y^(y-4))/(3z^7)#